Genetic Risk, Vascular Function, and Subjective Cognitive Complaints Predict Objective Cognitive Function in Healthy Older Adults: Results From the Brain in Motion Study - Amanda V. Tyndall; Amanda V. Tyndall; R. Stewart Longman; R. Stewart Longman; R. Stewart Longman; Tolulope T. Sajobi; Tolulope T. Sajobi; Tolulope T. Sajobi; Jillian S. Parboosingh; Jillian S. Parboosingh; Lauren L. Drogos; Lauren L. Drogos; et al. (Frontiers in Integrative Neuroscience, 2020)
Aging is associated with subjective memory complaints. Approximately half of those with subjective memory complaints have objective cognitive impairment. Previous studies have provided evidence of an association between genetic risk for Alzheimer’s disease (AD) and dementia progression. Also, aging is a significant risk factor for vascular pathology that may underlie at least some of the cognitive changes. This study investigates the relative contribution of subjective cognitive complaints (SCC), vascular function, and genetic risk for dementia in predicting objective cognitive performance. Multiple regression and relative importance analysis were used to investigate the relative contribution of vascular function, self-reported SCC, and dementia genetic risk, in predicting objective cognition in a sample of 238 healthy community-dwelling older adults. Age, sex, premorbid cognitive abilities, subjective verbal memory complaints, higher cerebrovascular blood flow during submaximal exercise, and certain dementia risk alleles were significant predictors of worse objective verbal memory performance (p < 0.001, R2 = 35.2–36.4%). Using relative importance analysis, subjective verbal memory complaints, and certain dementia risk alleles contributed more variance than cerebrovascular measures. These results suggest that age-related changes in memory in healthy older adults can be predicted by subjective memory complaints, genetic risk, and to a lesser extent, cerebrovascular function.